Papillary renal neoplasm with reverse polarity: A case report - Xing, Chengjuan; Tian, Hui; Zhang, Yunkun; Zhang, Li; Kong, Jixia (Frontiers in Oncology, 2023)
As a recently named rare renal tumor of epithelial origin, papillary renal neoplasm with reverse polarity (PRNRP) has unique histomorphological features and immunophenotypes, often associated with KRAS mutations and showing indolent biological behavior. In this study, we report a case of PRNRP. In this report, nearly all tumor cells were positive for GATA-3, KRT7, EMA, E-Cadherin, Ksp-Cadherin, 34βE12, and AMACR in varying intensities, focally positive for CD10 and Vimentin, while negative for CD117, TFE3, RCC, and CAIX. KRAS mutations (exon 2) were detected by amplification refractory mutation system polymerase chain reaction (ARMS-PCR), while no NRAS (exon 2-4) and BRAF V600 mutations (exon 15) were detected. A transperitoneal Robot-Assisted Laparoscopic Partial Nephrectomy was performed on the reported patient. No recurrence or metastasis was found during the 18 months of follow-up.